Research on the Media Image of Overseas Chinese in Latin American Countries based on the TV Series 'Surinam' - Guo, Wenjia (International Journal of Social Sciences and Public Administration, 2024)
As a multicultural Latin American country, Surinam holds an important position in commercial activities among overseas Chinese, but it is often marginalized in the media. The Korean drama "Surinam" showcases the multiculturalism of Surinam's overseas Chinese, but stereotypes still exist in media presentations. This study focuses on the media image of overseas Chinese and analyzes their image construction and dissemination in different cultural backgrounds. To enhance the effectiveness of cross-cultural communication, film and television works in the international communication context should face stereotypes in cross-cultural narratives and present the living conditions of different ethnic groups more realistically and comprehensively.